Software-Defined Radio-Based Modulation and Demodulation Scheme - Bakhraiba, Ahmed Mohamed Salih (2009)
Software Defined Radio (SDR) has been one of the new techniques developed to change the way the traditional wireless communication systems work. Through the definition of the SDR, this thesis aims at designing a modem system which can be adapted to many modulation schemes. Designing a multi-modulation schemes system in term of hardware will cost a lot and definitely consume power and increase the interference, and for this purpose, an adaptive algorithm is designed to be capable of detecting certain modulation schemes and identifying its type, and automatically demodulating the modulated signal after the decision of the identifier has been taken using digital signal processing techniques. Different digital modulation schemes were employed in this study for adaptation according to need. These include the Amplitude Shift Keying (ASK), Frequency Shift Keying (FSK), Binary Phase Shift Keying (BPSK), and Gaussian Minimum Shift Keying (GMSK). The adaptive system was mainly dependent on the following digital signal processing techniques: Continuous Wavelet Transform (CWT) and Fast Fourier Transform (FFT). For this purpose, the MATLAB was used as the simulation software throughout this thesis, where the SIMULINK tool had been used for the simulation of the demodulation process. The performance evaluation of the identification system, under each technique, had been derived in terms of signal-to-noise ratio (SNR) for the range from 4dB up to 15dB. Result's showed, the identification system was found to have a lower performance in identifying the ASK signal when using the CWT technique, particularly for low SNR value. Whereas the identification system could identify the ASK signal with the best performance using the FFT technique, even with the presence of high noise compared with other modulation schemes. Generally, most of the modulation schemes, under both techniques, have more than 90% accurate identification ability when the SNR is equal to and above 9dB. However, the identification ability of the system may vary from one modulation scheme to another, and from CWT to FFT; therefore, designing an identification system which combines both the techniques will be able to increase the ability for accurate identification.